THE EFFECT OF PRODUCT QUALITY, PRICE AND BRAND IMAGE ON THE PURCHASE DECISION OF JINISO PRODUCTS ON STUDENTS OF UNIVERSITAS MALIKUSSALEH - Tasya Ema Dwiyana; Heriyana; Syamsul Bahri; T.Edyansyah (RADJA PUBLIKA, 2025)
This research aims to analyze the influence of product quality, price and brand image on purchasing decisions for Jiniso products amongUniversitas Malikussaleh students. Jiniso, as a clothing brand that is popular among young people, needs to understand these factors to maintain its position in the market and attract consumers. The research method used is a quantitative approach with a sample collection technique using purposive sampling. Data was collected through a questionnaire distributed to 100 active student respondents at Universitas Malikussaleh who had ever purchased or used Jiniso products. Data analysis was carried out using multiple linear regression with the SPSS version 29.0 program. The variables studied include product quality, price and brand image, as well as how this third variable influences purchasing decisions. The results of this research show that product quality, price and brand image together have a positive and significant influence on the decision to purchase Jiniso products among Universitas Malikussaleh students. Product quality has a dominant influence, followed by brand image and price. These findings suggest that to improve purchasing decisions among students, Jiniso needs to focus on improving its product quality and brand image, while offering prices that match students' purchasing power. This research contributes to the development of effective marketing strategies to increase sales in the market and increase consumer satisfaction among Universitas Malikussaleh students.